Políticas de inclusão: reflexões sobre a inclusão de alunos surdos no IFAM Campus Parintins - (:unkn) unknown (Universidade Federal do Amazonas, 2022)
In the current paradigm of inclusive education, the growing number of students who are target audience of special education entering the spaces of regular education is perceptible and, in this direction, it is necessary to reflect on what has been done to solidify this effectiveness. This study started from the concern as a public servant and the perception from the observations in the classroom context. Thus, it is necessary to reflect on public educational policies, the legal parameters that guide the school inclusion of people with disabilities and, from this investigation, prove whether these rights are being guaranteed in practice. The vocational and technological education offered by IFAM aims to improve the quality of life of individuals, social inclusion and the construction of citizenship. In this perspective, it is worth recognizing the need for studies that encourage reflection on the inclusion of deaf students in the IFAM Campus Parintins and how it has been implemented. The general objective of this investigation process is to understand, through teaching practices, how policies for the inclusion of deaf students are developed in the IFAM CPA. The research was developed through a qualitative approach, built through theoretical study, case approach, elaboration of data collection instruments with the researched subjects using online questionnaires with open and closed, semi-structured questions. The target audience of the research consists of 6 teachers who had the presence of deaf students in the classroom, as well as 6 deaf students who studied at the Parintins campus, from 2015 to 2017. We used as a theoretical contribution global and national educational policies, as well as literature from important international, national, regional and local researchers, such as Skliar (1999), Jannuzzi (1992); Lopes (2011); Mantoan (1997, 2003, 2006, 2015); Mazzotta (2001, 2003); Perlin (2002), Sacks (1989); Sassaki (2002); Diniz (2007, 2009); Amoêdo (2017); Teixeira (2019), among others. Through this study, it was possible to achieve the proposed objectives that pointed to some results, such as: the need for training and information in the inclusive school context and the demand for interdisciplinary work, with systemic and continuous training that develops dialogue, participation and collaboration of education professionals. The importance of the Center for Assistance to People with Special Educational Needs (NAPNE) in its organizational and strategic structure is highlighted, as well as the need for a multidisciplinary team and support to collaborate in the construction of the educational development of deaf students. Finally, we consider that, knowing the identity of the deaf subject, as well as the deaf community and culture, which presents itself differently from the hearing culture, the collaborative work between managers, coordinators, teachers, interpreters and students are essential factors in what regarding the effective inclusion of deaf students in vocational technical courses.
Keywords: Educação especial; Contexto de sala de aula; Desenvolvimento educacional; Cultura ouvinte; Língua Brasileira de Sinais; CIÊNCIAS HUMANAS; Políticas Públicas Educacionais; Educação Inclusiva; Discentes Surdos; IFAM; Parintins